2009
DOI: 10.5012/bkcs.2009.30.12.3053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Extra Chloro Substituent on Photochemistry of o-Alkylphenacyl Chloride

Abstract: The title compound, α,α-dichloro-o-methylacetophenone, was prepared and its photochemical behavior was investigated. Addition of an extra chlorine at alpha position to the carbonyl showed many different features from photochemical reactivities of mono chloro analogue, 2,5-dimethylphenacyl chloride. In benzene, a rearrangement product with a formal 1,5-Cl shift and a reduction product were formed beside indanone. In methanol, solvolysis and cyclization of a common dienol intermediate occurred at comparable reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…67 Park and collaborators have recently shown that photolysis of 2,4,6-trialkylphenacyl benzoates can also lead to the corresponding benzocyclobutenols (6 in Scheme 5) in addition to indanones, 55 whereas irradiation of α-dichloro-2-acetophenone yields a mixture of various photoproducts. 68 Berkessel and co-workers used the photoenolization reaction as a tool to study the cyclization of 4′-benzophenone-substituted nucleoside derivatives as models for ribonucleotide reductases. 69 Klań and co-workers reported that the photolysis of 2-(alkoxymethyl)-5-methyl-α-chloroacetophenones (13) is very sensitive to traces of water in the solvent (Scheme 9).…”
Section: O-alkylphenacyl Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Park and collaborators have recently shown that photolysis of 2,4,6-trialkylphenacyl benzoates can also lead to the corresponding benzocyclobutenols (6 in Scheme 5) in addition to indanones, 55 whereas irradiation of α-dichloro-2-acetophenone yields a mixture of various photoproducts. 68 Berkessel and co-workers used the photoenolization reaction as a tool to study the cyclization of 4′-benzophenone-substituted nucleoside derivatives as models for ribonucleotide reductases. 69 Klań and co-workers reported that the photolysis of 2-(alkoxymethyl)-5-methyl-α-chloroacetophenones (13) is very sensitive to traces of water in the solvent (Scheme 9).…”
Section: O-alkylphenacyl Groupsmentioning
confidence: 99%
“…Klán and co-workers showed that photolysis of 4,5-dimethoxy-2-methylphenacyl benzoate can lead to the corresponding indanone derivative that is a precursor for the subsequent synthesis of donepezil, a centrally acting reversible acetylcholinesterase inhibitor used to treat Alzheimer’s disease . Park and collaborators have recently shown that photolysis of 2,4,6-trialkylphenacyl benzoates can also lead to the corresponding benzocyclobutenols ( 6 in Scheme ) in addition to indanones, whereas irradiation of α-dichloro-2-acetophenone yields a mixture of various photoproducts . Berkessel and co-workers used the photoenolization reaction as a tool to study the cyclization of 4′-benzophenone-substituted nucleoside derivatives as models for ribonucleotide reductases …”
Section: Arylcarbonylmethyl Groupsmentioning
confidence: 99%
“…Klán and co-workers showed that photolysis of a 4,5-dimethoxyphenacyl derivative can lead to an indanone precursor for the synthesis of donepezil . Wang and co-workers used this concept in polymer-supported synthesis, and Park and co-workers utilized this reaction in photopolymerization and the synthesis of various indanone and benzocyclobutenol derivatives. , …”
Section: Introductionmentioning
confidence: 99%